A Reconfigurable Nanophotonic Heterostructure Engineered by a DNA Origami Switch. Issue 10 (5th October 2022) - Ge, Huan; Yang, Donglei; Li, Yimeng; Wei, Yongji; Zhu, Xinyuan; Wang, Pengfei; Zhang, Chuan
Abstract: DNA origami has been widely used to construct nanophotonic structures due to its unparallel capability in assembling photonic nanomaterials with nanometer precision. Nevertheless, the majority of fabricated fluorescence‐based nanophotonic systems so far operate in the ultraviolet‐visible (UV‐Vis) region, which are accompanied by limitations of shallow penetration and potential light damage. Herein, we constructed a reconfigurable nanophotonic heterostructure by integrating an upconversion nanoparticle (UCNP) and a gold nanorod (AuNR) on a DNA origami switch (DOS) template. With the unique anti‐Stokes luminescence of UCNP whose excitation wavelength is mostly located in the near‐infrared (NIR) region, the obtained reconfigurable nanophotonic system can be excited by 980 laser light and generates visible light emission. In our nanophotonic system, the DNA origami template serves as a switch to reversibly tune the optical properties of UCNP. The construction of this nanophotonic heterostructure expands the toolbox of DNA origami‐based nanophotonic systems that may hold great potential in optical biosensing and imaging. Abstract : A reconfigurable nanophotonic heterostructure that can be excited by near‐infrared light was successfully constructed. By employing dynamic DNA origami switch (DOS) as a template and precisely organizing the upconversion nanoparticles (UCNPs) and gold nanorods (AuNRs) on it, the fluorescence of UCNPs can be reversibly tuned along with the conformational change of the DOS template, enabling the nanophotonic structure with potentials for biosensing.